Petrographical and Diagenesis Characterestics of Benavi Ironstone in Kurdistan Region- Northern Iraq - Yassin, Ali Taha; Mahmoud, Mudhafar M. (Sulaimani Journal for Pure and Applied Sciences, 2013)
Benavi Ironstone (BI) is hosted in highly fractured carbonate beds of Hadiena Formation and located about 20 kilometers N-NW of Amadiya District in Duhok Governorate – Kurdistan Region north of Iraq. The outcrop of BI extends about 2 kilometers with thickness up to 13 meters and occurs within Jurassic – Cretaceous sequence. Forty eight samples were collected from ten sections that represent this elongated body. Petrographical study under transmitted and reflected light microscopy showed that BI is related to algal-bioclastic-packstone host rocks; this facies suffered from many diagenetic processes such as iron oxides replacement, neomorphism, pyritization, dolomitization, silicification and phosphatization. Depending upon iron rich sediments textural classification, BI was also classified as iron-packstone. Iron oxides have replaced partially and completely the calcareous structures, consequently, deposits with unusual iron oxides contents, were produced. Pyrite is unevenly distributed throughout this body, which occurs in two patterns: euhedral massive and framboidal forms. Euhedral magnetite crystals are also present. Chamosite was mostly observed around impregnation fossils by iron oxides.
Keywords: ironstone; Iraq; Kurdistan; Benavi; ironpackstone